Reason, Revelation and Law in Islamic and Western Theory and History
XIV, 174 p.
Keywords: This book engages the diverse meanings and interpretations of Islamic and Western law which have affected people and societies across the globe, past and present, in correlation to the epistemological groundings of those meanings and interpretations. The volume takes a distinctively comparative approach, advancing dialogue on crucial transnational and global debates over the history of Western and Islamic approaches to law, politics and society and their relevance for today. It discusses how fundamental concepts are understood and even translated from one historical or political context or one semantic domain to another. The book provides focused studies of key figures and theories in a manageable, accessible format useful for specialized academic courses and research as well as general audiences. These analyses will prove beneficial to scholars and students of religious studies, interreligious, intercultural, and international relations, political science, history, sociology, and related fields both within and beyond the Western and Islamic worlds, as well as generally educated readers who take interest in these issues and their ramifications.